Sociocultural activities of wartime library within the context of the Ukrainian sociohumanitarian science priorities - Vasylenko Olha; Sereda Tetiana (Наукові праці Національної бібліотеки України імені В.І. Вернадського)

(untitled)
The purpose of the article is to examine legal documents of the National Academy of Sciences of Ukraine during full-scale war in Ukraine as a component of scientific and information source base for the libraries sociocultural activities and to highlight the organization of events on the corresponding topics in the leading scientific libraries. Research methods. The article employs general scientific (analysis, synthesis and generalization) and special methods (comparative, structural and component) based on the principles of the complexity, historicism and objectivity. Scientific novelty. The article justifies the use of the legal documents of the National Academy of Sciences of Ukraine as a component of the scientific and information source base for preparing thematic events within the sociocultural scientific library activities; examines the range of topics of the events in V. I. Vernadskyi National Library of Ukraine and in the other scientific libraries in relation to the legal acts of the National Academy of Sciences of Ukraine passed during the full-scale Russo-Ukrainian War as a part of countering Russian propaganda. Conclusions. Sociocultural activities, as one of the library functioning fields, aim to develop a spiritual culture, disseminate the relevant knowledge, represent the library and scientific resources, shape a positive institutional image; foster the realization of the task of building a scientific worldview, intellectual, moral and aesthetic development of society. The sociocultural activities of scientific libraries possess the powerful organizational, methodological and communicative instruments, which, using the scientific approach and documentary base, allows the libraries to engage in the information and knowledge struggle against the territory, political, economic and cultural expansion of an aggressor. An important component of the scientific and information base in preparing the thematic library events are the legal acts and other documents of the National Academy of Sciences of Ukraine, which highlight the relevant issues of the priority research fields, thereby guiding librarians in modern trends of the humanitarian knowledge development, its specific conceptual framework that is necessary for the justified document selection.